What is Different About Family Businesses? - Chami, Ralph (IMF Working Papers; Working Paper ;, 2001)
Family businesses make up forty percent of the Fortune 500 companies in the US, generate about two-thirds of the German GDP, employ about one-half of the labor force in Britain, and account for the majority of the private economies in developing countries. This paper develops a theory of family business that brings market forces and the family, as a nonmarket institution, under one rubric. The paper highlights and analyzes important factors, including product market competition, trust, and succession, which allow family businesses to thrive and to successfully compete with other businesses.